IMPLEMENTASI LIVE CHAT TAWK.TO UNTUK MENINGKATKAN RESPONSIVITAS LAYANAN PENGGUNA PADA WEBSITE SEKOLAH CIS BALI - Made Agus Putra Subali; I Gusti Rai Agung Sugiartha; I Putu Aditya Putra (Sewagati, 2025)
The CIS Bali School website is one of the platforms used to provide information for students, parents, prospective students, and the general public. The speed and quality of the information service provided are very important factors in improving the school's integrity. However, communication is currently carried out through traditional platforms such as telephone or WhatsApp, which often results in delays in delivering information to users. This community service activity aims to implement the Tawk.to live chat application on the CIS Bali School website as a solution to improve responsiveness and the quality of user services. The implementation method for this activity includes several stages, namely: (1) Initial coordination and needs analysis with the school; (2) Technical implementation by integrating the Tawk.to code into the website structure; (3) Dashboard configuration and feature customization according to the school's identity; and (4) Training and mentoring for designated staff or operators to operate the chat service effectively. Based on the activities that have been carried out, the Tawk.to service has been successfully integrated into the CIS Bali School website, and the training and assistance in using the Tawk.to application has been well understood by the assigned operators.